(untitled) (Revista Educação, Artes e Inclusão, 2023)
In the thematic interface between the field of education and film studies, the aim of this article is to bring the theme of the double through the cinema, as one of the ways of life of the contemporary, where there is the doubling of the self as an attempt to relate to the real . As a methodology, the Deleuzian cartography and the analytic of tragic hermeneutics were used. The film "O Duplo" (2013, Ayode) was analyzed for this. It was noted by the cartographic gesture that the film, when focusing on the ontological resource of the creation of a duplication of the real, by the emergence of the protagonist’s double, ends up becoming an attempt of existential elaboration in the face of the contemporary malaise, crossed by nihilism and social decay. In this sense, the article explains this way of life as illusory, based on the pertinent reading of Clement Rosset, which characterizes this fragile output of contemporary being, to make explicit the inability of this man to deal with the nihilistic atmosphere of today, which escapes by the use of the doubling of the real or of itself.